PENERAPAN MODEL FUGASITAS PADA PENCEMARAN DDT DI WADUK SAGULING - Yandes Panelin (President University, 2016)
Saguling reservoir is an artificial reservoir located in West Bandung regency at an altitude of 643 m above sea level and serves to stem the Citarum River which is the largest river in West Java. Upper Citarum River has detected the organochlorine insecticide, one of them iss DDT. It is feared that DDT can accumulate in Saguling Reservoir which is the first dam to stem the Citarum River. This is very worrying given Saguling has greatly affect to the lives of many people. This study was conducted to estimate the fugacityvalue and concentration of DDT in each environmental compartment, such as in water, sediment, fish, aquatic plants, and mollusks by using Fugacity models. From calculation result, average DDT fugacity in the air is 3.23.10-14Pa, on the soil 2.73.10-17Pa, in the water 1.78.10-9 Pa, in sediments 9.64.10-10Pa. DDT concentration in the air compartment at Saguling Reservoir is 9,1.10-12ppm, on the ground 4,5.10-11ppm, in the water 6,9.10-4ppm, in sediments 0.99ppm, in the fish 0.013ppm, in the aquatic plant 0.005ppm, and in the mollusk 0.002ppm. Fugacity models are useful in predicting the distribution of DDT in each environmental compartment in Saguling Reservoir.